Everything I Know About You - Dee, Barbara (New York Aladdin, 2018)
"Misfit Tally is forced to room with queen bee Ava on the seventh grade's extended field trip to Washington, D.C., and discovers several surprising things about her roommate, including the possibility of an eating disorder"--
Includes bibliographical references (pages 305-306).
Keywords: Interpersonal relations in adolescence -- Juvenile fiction; Friendship in adolescence -- Juvenile fiction; School field trips -- Juvenile fiction; Eating disorders in adolescence -- Juvenile fiction; Interpersonal relations -- Fiction; Friendship -- Fiction; School field trips -- Fiction; Anorexia nervosa -- Fiction; Washington (D.C.) -- Juvenile fiction; Washington (D.C.) -- Fiction